Egg Production of Cherax quadricarinatus (von Martens, 1868) in Lido Lake, West Java : Produksi Telur Cherax quadricarinatus (von Martens, 1868) di Danau Lido, Jawa Barat - Martin Ali Iqbal; Isdradjad Setyobudiandi; Majariana Krisanti; Yusli Wardiatno (Tropical Fisheries Management Journal, 2019)
Cherax quadricarinatus is one of the important fisheries commodities in Lido Lake, but this spesies often become invasive. Egg production is used as basic information for managing freshwater cryfish in Lido Lake. This study aims to analyze the egg production of freshwater crayfish Cherax quadricarinatus in the waters of Lido Lake Bogor, West Java Province. This research was conducted in December 2017 until February 2018 with a total sample of 101 females. The growth pattern of Cherax quadricarinatus based on the t-test is negative allometric. Different carapace lengths have a significant effect on the total number of eggs. The average number of eggs produced during the three months sampling was 212 ± 65 eggs. The average egg volume produced is 4,2376 ± 1,2270 mm3 and the average egg diameter produced is 1,9919 ± 0,1869 mm.